Bergman cyclization of main-chain enediyne polymers for enhanced DNA cleavage. Issue 23 (25th May 2022) - Cai, Yue; Lehmann, Florian; Peiter, Edgar; Chen, Senbin; Zhu, Jintao; Hinderberger, Dariush; Binder, Wolfgang H.
Abstract : The design of novel polymers bearing multiple ene-diynes in the main chain are reported, allowing to tune activity of DNA cleavage via the Bergman cyclization. Abstract : Since the discovery of the role of enediynes in natural antibiotics (such as calicheamicines) via in situ diradical-induced DNA strand cleavage, Bergman cyclization has attracted fervent attention for decades. Thus, Bergman cyclization is widely used in pharmaceutics, synthesis, and polymer chemistry as a trigger for the generation of diradicals. Whereas applications of the Bergman cyclization in polymers mostly rely on side-chain linked enediynes, strategies to embed enediynes as the main repeating units into polymers are not reported yet. Here, the synthesis of main-chain enediyne polymers was accomplished, allowing to embed and control the reactivity of the diamino enediynes via polycondensation into polyimines. Such main-chain enediyne polymers in solution exert a chain-length dependent DNA cleavage activity under physiological conditions, additionally tunable by modulating the stereoelectronic environment via their substitution patterns. Photochemical activation generates long-lived free radicals as verified via electron paramagnetic resonance (EPR) spectroscopy, with rates of their formation comparable to those in DNA cleavage experiments.